Feministic Approach of Saint Poetess of Varkari Sampradaya: : An Appraisal - Puradkar, Rina Avinash Pitale (Dia-noesis: A Journal of Philosophy, 2025)
Feminism seeks not to divide genders but to empower women to progress alongside men, challenging social inequalities and asserting women’s autonomy, identity, and equal rights across all spheres of life. Its core aim is to transform gender-biased societal mindsets and patriarchal structures, promoting an egalitarian society. In Maharashtra, the varkari sect embodies values of humanism, liberty, and gender equality. Amid periods of moral decline, the teachings of varkari saints offered ethical direction. Notably, female saint-poetesses of the varkari tradition, from the 13th century, used devotional literature as a tool to resist social injustice and advocate for women’s dignity. Their spiritual and literary contributions provided a progressive voice in a deeply patriarchal society and continue to inspire today. This paper evaluates the role of these saint-poetesses in furthering women’s emancipation, highlighting how their legacy aligns with feminist ideals and remains vital in ongoing struggles for gender equality.